Noonan Syndrome Presenting as Lymphoedema Precox (Journal of Medicine, 2012)
Noonan Syndrome is an autosomal dominant disorder characterized by short stature, typical facial features and congenital heart defects. Other associated features are webbed neck, chest deformity, mild intellectual deficit, cryptorchidism, bleeding tendency and lymphatic dysplasia. We are reporting a 13 year old boy of Noonan syndrome presenting with lymphoedema of lower limb and genitalia. DOI: http://dx.doi.org/10.3329/jom.v13i2.12771 J Medicine 2012; 13 : 243-245